INOVASI PELAYANAN ADMINISTRASI KEPENDUDUKAN “PANTAI BALIKPAPAN” DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KOTA BALIKPAPAN - Diansyah, Rahma; Idris, Adam; Noor, Muhammad (Jurnal Administrative Reform, 2024)
This research aims to explain, analyze and interpret the implementation of the Population Administration Service Innovation "Balikpapan Beach" in the Balikpapan City Population and Civil Registry Service. This research focuses on implementing innovation through the Best Practice Innovation approach (Impact, Partnership, Sustainability, Leadership, Transferability) and its Inhibiting Factors. The results of the research show that the Population Administration Service Innovation "Balikpapan Beach" in the Balikpapan City Population and Civil Registration Service is good and is included in the Best Partice category including the Impact dimension on the external (Community) and Internal (Balikpapan City Dukcapil) side, the Balikpapan City Dukcapil Patnership dimension collaborate with related departments and private parties through cooperation agreements. Sustainability support from the legislative side, the issuance of supporting regulations as well as support from HR commitment and openness to suggestions and criticism of services as evaluation material. = Leadership of the Head of the Balikpapan City Dukcapil Service is the key to the success of the "Balikpapan Beach" innovation with leadership in the Transformational and Agile leadership categories. And finally, the transferability dimension of the "Balikpapan Beach" application has been replicated and studied/transferred from knowledge with agencies inside and outside East Kalimantan. The inhibiting factors are limited operational hours, the public's lack of understanding of the "Balikpapan Beach" service, resulting in people returning in droves to the Balikpapan City Dukcapil to get clarity regarding complaints and service information and finally the centralized SIAK Server which is directly run by the Directorate General of Dukcapil, Ministry of Home Affairs, which experienced disruption and maintenance resulting in disruption of services at "Balikpapan Beach".